Evaluation of the anti-cancer activity of the triterpenoidal saponin fraction isolated from the traditional Chinese medicine Conyza blinii H. Lév. Issue 6 (13th January 2017) - Ma, Long; Liu, Haiyan; Meng, Lingpei; Qin, Ping; Zhang, Botao; Li, Yuyin; Man, Shuli; Liu, Zhen; Liu, Zhenxing; Diao, Aipo
Abstract : Triterpenoidal saponins fraction isolated from a traditional Chinese medicine Conyza blinii H. Lév. demonstrates anti-cancer activity both in vitro and in vivo . Abstract : Conyza blinii H. Lév. is traditionally used in China as a medicinal plant to treat inflammation. We show here that the active fraction of this plant, Conyza blinii saponin (CBS), also has potent anti-cancer activity both in vitro and in vivo . Cell-based experiments showed that CBS suppresses the growth of cancer cells in a number of ways. CBS induces apoptosis in a dose-dependent manner. The mitochondrial membrane potential (Δ Ψ m ) can be disrupted by CBS, which indicates activation of the mitochondrial apoptosis pathway. This was confirmed by an increase in the number of apoptotic bodies seen with scanning electron microscopy. CBS is capable of inhibiting cancer cell migration and invasion. Flow cytometry experiments demonstrated that CBS causes S phase arrest in cancer cells. These effects collectively led to an inhibitory activity against HeLa cells. In vivo animal experiments were carried and showed that 15 mg kg −1 CBS is a tolerable dose and reduced the tumour weight by 70% in a 10 day administration regimen.